Analysis of cumulative energy demand and carbon footprint in residential building structures. (2018) - Fraile-García, E.; Ferreiro-Cabello, J.; Marrodán-Esparza, F.J.; Jiménez-Macías, E.
This paper assesses the impact of the arrangement of pillars and building height in residential building structures and its effect on the environmental impacts of the structural solution. Impacts are analysed in the elements of the structure: foundations, pillars (or columns), and slabs. The manufacturing process of materials and the process of implementation of the proposed structure are measured by using both embodied energy and carbon footprint. The results are obtained per executed square meter. The analysis provides the optimal arrangement for the pillars and the height of the building; the increase in separation of the pillars causes greater impacts, and the design of tall buildings also drives to an important increase of resource consumption. The blocks in which the structures were split have different weights. The most representative are the slabs, around 80% compared to 7% of the pillars and 13% of the foundations. The decisions made in the layout of pillars in the design phase have a different impact on the items of the structure, and their analysis and assessment are developed in this work.